Analisis Sumber Daya Manusia Pemerintahan: Pengembangan Potensi Kelurahan Sarirejo - Wijaya, Dian; Rum Mawangi, Azzara; Muhaimin, Admin (MAJAPAHIT POLICY, 2024)
Government human resources (HR) have enormous potential for economic growth and prosperity. The competitiveness and capacity of a village can be increased with the help of highly educated and superior quality personnel. The role of local government in planning and managing development programs to optimize village potential is very important. To optimize development, collaboration and coordination of government human resources is required. The purpose of monitoring and evaluating development programs is to ensure alignment with established goals. Human resource management which focuses on planning and utilizing human resources is very important for achieving the organization's vision and mission. Sarirejo Village, Mojosari District has quite large potential for developing human resources (HR). This recognition cannot be separated from the productive efforts of Sarirejo residents in improving educational achievement. Sarirejo Subdistrict has the potential for MSME growth. Sarirejo Subdistrict has held various skills development training activities for the community, including socialization on making halal certificates to develop existing MSMEs so that they can transition into the medium business category. In the digital era, human resource development also requires collaboration between management, employees and digital platform service providers. Collaboration is critical to the successful implementation of digital HR administration.